Lateral flow devices for samples collected by straw sampling method for postmortem canine rabies diagnosis - Milagros R. Mananggit; Daria L. Manalo; Nobuo Saito; Kazunori Kimitsuki; Alyssa Marie G. Garcia; Patricia Mae T. Lacanilao; Joely T. Ongtangco; Cornhlo R. Velasco; Maria Victoria A. del Rosario; Maria Glofezita O. Lagayan; Kentaro Yamada; Chun-Ho Park; et al. (Public Library of Science (PLoS), 2021)
The direct fluorescent antibody test (dFAT) using brain sample after opening the skull is the standard rabies diagnostic test in animal rabies. However, it is not feasible in many resource-limited settings. Lateral flow devices (LFD) combined with a simple sampling methodology is quicker, simpler, and less hazardous than the standard test and can be a useful tool. We conducted a prospective on-site study to evaluate the diagnostic accuracy of the LFD with the straw sampling method compared with that of the dFAT with the skull opening procedure for post-mortem canine rabies diagnosis. We collected 97 rabies-suspected animals between December 1, 2020 and March 31, 2021. Among the 97 samples, 53 and 50 cases were positive tests for dFAT and LFD, respectively. The sensitivity and specificity of LFD with straw sampling method were 94.3% (95% confidence interval [CI], 84.3-98.8%) and 100% (95% CI, 92.0-100%), respectively. The performance of LFD by the straw sampling method showed relatively high sensitivity and 100% specificity compared with that of dFAT performed on samples collected after opening the skull. This methodology can be beneficial and is a strong tool to overcome limited animal surveillance in remote areas. However, because of our limited sample size, more data using fresh samples on-site and the optimizations are urgently needed for the further implementation in endemic areas.